Faith in flux: how youths navigate Pentecostalism's growth in Singapore - Lim, Prudence En-Song (Nanyang Technological University, 2024)
In Singapore's dynamic religious landscape, Pentecostalism is witnessing notable growth, particularly among young adults seeking deeper and more experiential forms of faith. This feature writing package, titled "Faith in Flux: How Youths Navigate Pentecostalism’s Growth in Singapore," explores the engagement of young believers with Pentecostal churches, known for their vibrant worship and emphasis on personal encounters with the Holy Spirit. The package explores the appeal and tensions as these young adults navigate their faiths in the Pentecostal belief and churches. The term "Pentecostal" is used broadly to encompass churches that highlight the gifts of the Holy Spirit, including healing and prophecy, while acknowledging the nuanced distinctions within the broader charismatic movement.